To solve this system of equations using substitution, we can rearrange the first equation to solve for y in terms of x:
y = 2 - 3x
Now, substitute this expression for y into the second equation:
7x - 4(2 - 3x) = 30
7x - 8 + 12x = 30
19x - 8 = 30
19x = 38
x = 2
Now that we have found the value of x, we can substitute it back into the expression we found for y earlier:
y = 2 - 3(2)
y = 2 - 6
y = -4
Therefore, the solution to the system of equations is x = 2 and y = -4.
Solving equations using substitution quick check
Solve the system of equations. 3x + y = 2; 7x - 4y = 30 (1 point)
1 answer